EXPERIMENTAL STUDY CONCERNING THE DISTRIBUTION OF GRANULAR PARTICLE SHAPE FROM A FILTER LAYER - OANA IRIMIA; VALENTIN NEDEFF; MIRELA PANAINTE LEHĂDUŞ; CLAUDIA TOMOZEI (Journal of Engineering Studies and Research)
The shape of granular particle from a filter layer represent a determinant factor regarding the efficiency of filtration process. In order to adequately predict the efficiency of granular filters is necessary to know the distribution of granular particle shape from filter layer. This paper presents a small study - in terms of experimental results, but laborious - in terms of sample preparation, regarding the identification of distribution by shape classes of granular particles from a filter layer. For experimental determinations have been used perlite and anthracite - two granular filter materials. It has been analyzed in terms of particle shape 1,000 particles of perlite and 1,000 particles of anthracite taken randomly from each filter layer. It has been observed that spherical particles have an average distribution for two type filter materials.